Local effect of allopregnanolone in rat ovarian steroidogenesis, follicular and corpora lutea development - Cáceres Gimenez, Antonella Rosario Ramona (2024)
Allopregnanolone (ALLO) is a known neurosteroid and a progesterone metabolite synthesized in the ovary, CNS, PNS, adrenals and placenta. Its role in the neuroendocrine control of ovarian physiology has been studied, but its in situ ovarian effects are still largely unknown. The aims of this work were to characterize the effects of intrabursal ALLO administration on different ovarian parameters, and the probable mechanism of action. ALLO administration increased serum progesterone concentration and ovarian 3β-HSD2 while decreasing 20α-HSD mRNA expression. ALLO increased the number of atretic follicles and the number of positive TUNEL granulosa and theca cells, while decreasing positive PCNA immunostaining. On the other hand, there was an increase in corpora lutea diameter and PCNA immunostaining, whereas the count of TUNEL-positive luteal cells decreased. Ovarian angiogenesis and the immunohistochemical expression of GABAA receptor increased after ALLO treatment. To evaluate if the ovarian GABAA receptor was involved in these effects, we conducted a functional experiment with a specific antagonist, bicuculline. The administration of bicuculline restored the number of atretic follicles and the diameter of corpora lutea to normal values. These results show the actions of ALLO on the ovarian physiology of the female rat during the follicular phase, some of them through the GABAA receptor. Intrabursal ALLO administration alters several processes of the ovarian morpho-physiology of the female rat, related to fertility and oocyte quality.